The Effect of Competence and Independence on Professional Skepticism and Audit Quality - Erwin Hadisantoso; Emillia Nurdin; Mulyati Akib (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study empirically examines the influence of competence and independence on professional skepticism and its relationship to audit quality (BPKP Representative Office of South Sulawesi Province). This research is descriptive quantitative research, which uses primary data. The sample of this research is the Auditor of the BPKP Representative Office of South Sulawesi Province, amounting to 46 people. The hypothesis test used is Structural Equation Modeling (SEM) analysis based on variance, namely Partial Least Square (PLS). The results of this study indicate that competence has a positive and significant effect on professional skepticism, independence has a positive and significant effect on professional skepticism, competence has a positive and significant impact on audit quality, independence has a positive and significant effect on audit quality and professional skepticism has a positive impact and essential to audit quality.